The Discretionary power of first instance criminal court in Appreciating the facts of the penal Action in Algerian legislation - Rahal, Mohamed Tahar (Journal of Human Sciences, 2023)
There are limitations on first instance criminal court when exercising its authority in appreciating the penal action facts; the court is entitled to deal exclusively whith the facts contained in the referral decision issued by the Accusation chamber which must include a description of the facts and their is judicial qualification under penalty of nullity, and the referral decision must be notified to the accused. The criminal court, in addition to grant a judicial qualification to the facts consolidated whith the appropriate legal provision, can as well, modify the description of the charges, and also, amend the charges by adding the aggravating circumstances, even if these circumstances were not indicated in the referral decision, and finally, it is entitled to correct the material errors and rectify the omissions in the expression of the accusation.